Arthropod Community Structure Indicating Soil Quality Recovery in the Organic Agroecosystem of Mount Ciremai National Park’s Buffer Zone - Kurniawan, Isma Dwi; Kinasih, Ida; Akbar, Rahmat Taufiq Mustahiq; Chaidir, Liberty; Iqbal, Sawaludin; Pamungkas, Bayu; Imanudin, Zikri (Caraka Tani: Journal of Sustainable Agriculture, 2023)
The Mount Ciremai National Park (TNGC) buffer zone is designed to support conservation efforts. However, agriculture in this area is dominated by conventional farming that excessively uses synthetic fertilizers, which threatens soil quality. Introducing an organic fertilizer and plant growth-promoting rhizobacteria (PGPR) is expected to enhance soil quality recovery in this area. This study aimed to analyze the differences in soil arthropod communities between organic and conventional agriculture and a forest in the TNGC buffer zone to assess soil quality improvement generated by the application of the organic fertilizer and PGPR. Soil arthropods were collected with Berlese-Tullgren funnels and pitfall traps. Several associated environmental parameters, including soil pH, C-organic, temperature, and moisture, were also measured. Data were analyzed using ecological indices (i.e., richness, diversity, evenness, dominance, similarity) and soil biological quality (QBS-ar). Non-metric multidimensional scaling (NMDS) was performed to examine the relation of arthropods with environmental parameters. In total, 957 individuals of soil arthropods belonging to four classes and 15 orders were recorded. Berlese-Tullgren and pitfall traps resulted in a similar tendency in most variables, with higher richness, diversity, and evenness values in the forest, followed by organic and conventional habitats. In addition, similarity and QBS-ar indicated that forest and organic communities were more similar than conventional community. C-organic, soil moisture and pH were considered the most deciding environmental parameters for arthropod assemblages. All measured variables in this study illustrated better soil quality in organic than in conventional agriculture. This study implicates the benefit of utilizing organic fertilizers and PGPR for soil quality restoration in agroecosystems.